MiR-495-3p promotes cardiac hypertrophy by targeting Pum2: miR-495-3p/Pum2 axis in CH - Yu, Shushu; Wang, Mingliang; Xie, Yun; Wang, Bo; Xu, Yawei (Cellular and Molecular Biology, 2024)
Pathological cardiac hypertrophy (CH) may lead to heart failure and sudden death. MicroRNAs (miRNAs) have been documented to play crucial parts in CH. The objective of this research was to discuss the potential along with molecule mechanism of miR-495-3p in CH. In vivo CH model was induced by aortic banding (AB) in rats. Cellular hypertrophy in H9c2 rat cardiomyocytes was stimulated by angiotensin II (Ang II) treatment. Haematoxylin and eosin (HE), echocardiography and immunofluorescence staining were used to examine the alterations in cardiac function. The outcomes showed that miR-495-3p expression was high in rat model as well as in Ang II-stimulated cardiomyocytes. Besides, silenced miR-495-3p attenuated CH both in vitro and in vivo. Mechanically, miR-495-3p bound to pumilio RNA binding family member 2 (Pum2) 3’UTR and silenced its expression. Rescue assays further notarized that Pum2 silence abrogated the inhibitory impacts of miR-495-3p inhibitor on CH. In a word, the present research uncovered that miR-495-3p promoted CH by targeting Pum2. Therefore, miR-495-3p may be a novel therapeutic molecule for this disease.